2002
DOI: 10.3171/spi.2002.96.3.0346
|View full text |Cite
|
Sign up to set email alerts
|

Dual-strap augmentation of a halo orthosis in the treatment of atlantooccipital dislocation in infants and young children

Abstract: ✓ Two children who were 13 months and 3 years old and who had suffered traumatic atlantooccipital dislocation were each treated by being placed in a halo orthosis for 10 weeks. Because of a continued loss of reduction due to the poor fit of the halo vest, a dual-strap augmentation was developed. This strap augmentation allowed consistent reduction to be maintained. Both children were therefore successfully treated nonsurgically with a halo vest. One child remained neurological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Sixth nerve palsy is the most common cranial nerve injury. Another common cranial nerve palsy is the hypoglossal nerve [5,8,17,29,30]. Such neuropathy is probably induced by the sudden axial distraction on the nerves and medulla, or injury of cranial nerve nuclei [5,7,8,31].…”
Section: Discussionmentioning
confidence: 99%
“…Sixth nerve palsy is the most common cranial nerve injury. Another common cranial nerve palsy is the hypoglossal nerve [5,8,17,29,30]. Such neuropathy is probably induced by the sudden axial distraction on the nerves and medulla, or injury of cranial nerve nuclei [5,7,8,31].…”
Section: Discussionmentioning
confidence: 99%
“…Conservative treatment with extension or halo-fixator as further management is recommended in children and in the case of little instability of AOD [2,28,49,56,63,73,83,84,93]; however, from the aforementioned literature it is not evident how much instability may be tolerated. In children, a fibrous ankylosis is expected after months of conservative treatment [49,56,83,93]. In adults and with increasing instability, a short dorsal spondylodesis should be performed [15,34,68,82,93].…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Most investigators recommend a regime of conservative treatment with a halo frame in children, especially if there is little instability. 7,20,21,24 However, others think that these measures are insufficient and advocate immediate internal fixation. 4,5,19 It is suggested that halo immobilization alone is insufficient and can give a chronic unstable situation, eventually requiring operative fixation.…”
Section: Treatmentmentioning
confidence: 97%